Incidence of healthcare-associated coronavirus disease 2019 (COVID-19) in the state of Geneva. (25th February 2023) - Mongin, Denis; Catho, Gaud; Iten, Anne; Harbarth, Stephan; Courvoisier, Delphine S.
Abstract: An examination of all coronavirus disease 2019 (COVID-19) cases and patient movements in Geneva indicated important disease activity within the healthcare system since the beginning of the pandemic. We estimate that 4.3% of all COVID-19 cases were likely acquired within the healthcare system, contributing to 62% of the COVID-19–related deaths.